A short history of neuroendocrine tumours and their peptide hormones. Issue 1 (January 2016) - de Herder, Wouter W.; Rehfeld, Jens F.; Kidd, Mark; Modlin, Irvin M.
Abstract : The discovery of neuroendocrine tumours of the gastrointestinal tract and pancreas started in 1870, when Rudolf Heidenhain discovered the neuroendocrine cells, which can lead to the development of these tumours. Siegfried Oberndorfer was the first to introduce the term carcinoid in 1907. The pancreatic islet cells were first described in 1869 by Paul Langerhans. In 1924, Seale Harris was the first to describe endogenous hyperinsulinism/insulinoma. In 1942 William Becker and colleagues were the first to describe the glucagonoma syndrome. The first description of gastrinoma by Robert Zollinger and Edwin Ellison dates from 1955. The first description of the VIPoma syndrome by John Verner and Ashton Morrison dates from 1958. In 1977, the groups of Lars-Inge Larsson and Jens Rehfeld, and of Om Ganda reported the first cases of somatostatinoma. But only in 2013, Jens Rehfeld and colleagues described the CCK-oma syndrome. The most recently updated WHO classification for gastrointestinal neuroendocrine tumours dates from 2010.